The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/angeo-35-25-2017
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the total ozone column using a Brewer spectrophotometer and TOMS and OMI satellite instruments over the Southern Space Observatory in Brazil

Abstract: Abstract. This paper presents 23 years of quasi-continuous measurements of the total ozone column (TOC) over the Southern Space Observatory (SSO) in São Martinho da Serra, Brazil (29.26 • S, 53.48 • and 488 m altitude). The TOC was measured by a Brewer spectrometer, and the results are also compared to daily and monthly observations from the TOMS (Total Ozone Mapping Spectrometer) and OMI (Ozone Monitoring Instrument) satellite instruments. Analyses of the main interannual modes of variability computed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 64 publications
4
29
1
3
Order By: Relevance
“…In addition, the instrument measures pressure and cloud cover. Peres et al (2017) reported good cor- relation between these two types of data used, surface instrument (Brewer) and satellite instrument (OMI), which further confirms the reliability of these data for the study region.…”
Section: Study Region Instruments and Methodologysupporting
confidence: 72%
“…In addition, the instrument measures pressure and cloud cover. Peres et al (2017) reported good cor- relation between these two types of data used, surface instrument (Brewer) and satellite instrument (OMI), which further confirms the reliability of these data for the study region.…”
Section: Study Region Instruments and Methodologysupporting
confidence: 72%
“…2). The methodology used for the launch followed a pattern used in Natal-RN (5.79 • S, 35.20 • W) in a study by Witte et al (2017). The measurements collected by the sounding balloon used here were ozone and temperature.…”
Section: Methodology and Instrumentsmentioning
confidence: 99%
“…This ground-based device can make as many as 40 measurements per day depending on the weather conditions. On 21 October 2016 (295 on the Julian calendar), the Brewer performed 15 measurements, which are considered valid according to the operation of the instrument (Vaz Peres et al, 2017) as well as the days before and after the launch.…”
Section: Methodology and Instrumentsmentioning
confidence: 99%
“…Daily averages of the Brewer TOC were compared with satellite ozone values obtained during the overpass. The use of daily means instead of Brewer TOC observations taken close to the OMI overpass is reasonable since it allows a large number of pair measurements to be compared (Antón et al, 2009;Vaz Peres et al, 2017) because there are only one or two daily satellite values.…”
Section: Satellite Toc Datamentioning
confidence: 99%